(untitled) (Indonesian Economic Justice Review, 2025)
This paper investigates the growing issue of foreign debt in Indonesia and its long-term implications for economic justice. As Indonesia’s economy continues to expand, the government has increasingly relied on foreign loans to finance infrastructure projects, social programs, and development initiatives. However, the sustainability of this debt has raised concerns about the future economic sovereignty of the country and the equitable distribution of the benefits of development. The study explores how the government’s borrowing practices impact future generations, particularly in terms of economic growth, debt servicing, and social equity. Through a review of Indonesia’s foreign debt portfolio, including the sources of loans, interest rates, and repayment terms, the paper assesses whether the benefits derived from these loans outweigh the long-term costs. The paper also examines the social and economic implications of rising debt, particularly for marginalized populations who are unlikely to benefit from large-scale infrastructure projects. The findings highlight that while foreign debt can stimulate development in the short term, excessive reliance on borrowing could exacerbate inequalities, place an undue burden on future generations, and hinder sustainable economic growth. The paper concludes with policy recommendations for balancing debt management with long-term economic justice and sustainable development goals.